Sequencing Analysis of Plasma Epstein-Barr Virus DNA Reveals Nasopharyngeal Carcinoma-Associated Single Nucleotide Variant Profiles - Lam, W K Jacky; Ji, Lu; Tse, O Y Olivia; Cheng, Suk Hang; Jiang, Peiyong; Lee, P H Patrick; Lin, S Vivien; Hui, Edwin P; Ma, Brigette B Y; Chan, Anthony T C; Chan, K C Allen; Chiu, Rossa W K; et al. (Clinical chemistry (Baltimore, Md.), 2020)
Abstract Background Nasopharyngeal carcinoma (NPC) is strongly associated with Epstein-Barr virus (EBV) infection. Plasma EBV DNA is a validated screening tool for NPC. In screening, there are some individuals who do not have NPC but carry EBV DNA in plasma. Currently it is not known from screening if there may be any genotypic differences in EBV isolates from NPC and non-NPC subjects. Also, low concentrations of EBV DNA in plasma could pose challenge to such EBV genotypic analysis through plasma DNA sequencing. Methods In a training dataset comprised of plasma DNA sequencing data of NPC and non-NPC subjects, we studied the difference in the EBV single nucleotide variant (SNV) profiles between the two groups. The most differentiating SNVs across the EBV genome were identified. We proposed an NPC risk score to be derived from the genotypic patterns over these SNV sites. We subsequently analyzed the NPC risk scores in a testing set. Results A total of 661 significant SNVs across the EBV genome were identified from the training set. In the testing set, NPC plasma samples were shown to have high NPC risk scores, which suggested the presence of NPC-associated EBV SNV profiles. Among the non-NPC samples, there was a wide range of NPC risk scores. These results support the presence of diverse SNV profiles of EBV isolates from non-NPC subjects. Conclusion EBV genotypic analysis is feasible through plasma DNA sequencing. The NPC risk score may be used to inform the cancer risk based on the EBV genome-wide SNV profile.